2014
DOI: 10.1051/kmae/2014012
|View full text |Cite
|
Sign up to set email alerts
|

Assessing the influence of source distance and hydroecoregion on the invertebrate assemblage similarity in central Italy streams

Abstract: Key-words:HER, macroinvertebrate, monitoring, source distance, watercourse Increasing the river habitat safeguard level is one of the main actions proposed by the European Water Framework Directive in the field of biomonitoring. To do so, watercourses within the same hydroecoregions (that is, homogeneous areas based on climate, geology and topography) ought to be compared. In addition, the source distance was thought to play an important role in comparing rivers and then planning monitoring activities. The pur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 38 publications
0
4
0
Order By: Relevance
“…factors that influenced the study river basin, as previous studies have shown (Álvarez-Cabria et al, 2011;Traversetti and Scalici, 2014). The macroinvertebrate density and diversity both showed a decreasing trend with the pollution increase.…”
Section: Community Patterning and The Environmental Predictorsmentioning
confidence: 62%
“…factors that influenced the study river basin, as previous studies have shown (Álvarez-Cabria et al, 2011;Traversetti and Scalici, 2014). The macroinvertebrate density and diversity both showed a decreasing trend with the pollution increase.…”
Section: Community Patterning and The Environmental Predictorsmentioning
confidence: 62%
“…In each sampling site, the water was sampled by a plankton net with a mesh size of 80 μm and a diameter of 13 cm. Water velocity (cm s -1 ) was measured by flowmeter General Oceanics 2030 series [31]. The net was held against the current in the middle of the river 13 cm below the water surface for maximum 1 minute (Supplementary Figure S1).…”
Section: Sampling Of Water Sediments and Macroinvertebratesmentioning
confidence: 99%
“…A representative 10 m sub-reach in the lower part of the reach was selected, and the proportions of substrate in this sub-reach were estimated. Macroinvertebrate sampling included 10 sampling units (see [35,36]) and was performed using a hand net (25 × 25 cm, mesh size 0.5 mm). Sampling plots of 25 × 25 cm were allocated to representative substrata according to their cover at the sampling site, and the "kick-sampling" method was used.…”
Section: Sampling and Analysismentioning
confidence: 99%